Три добруджански рода Three families of the Dobrouja - Lyubomir D Penev (Pensoft Publishers, 2016)
This richly illustrated book tells the story of three families of the Dobrouja - the Netezilovi family, the Mangozovi family and the Vikovi family. Along with the many old and new photographs, it presents a number of family trees and includes a paragraph about each of the family members. The issue also includes several short stories by Lyubomir Penev, based on memories from his childhood.